2011
DOI: 10.1111/j.1472-765x.2011.03141.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of loop-mediated isothermal amplification and real-time PCR for the diagnosis of tuberculous pleurisy

et al.

Abstract: Aims:  Tuberculous pleurisy is an important cause of pleural effusions in areas with a high incidence of tuberculosis. In this study, we developed an IS1081‐based LAMP for the detection of Mycobacterium tuberculosis complex and investigated its usefulness in the diagnosis of tuberculous pleurisy. Methods and Results:  Investigation of pleural effusion samples from patients with tuberculous pleurisy, majority of them smear‐/culture‐negative, and control individuals with non‐TB diseases showed that the LAMP assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Slightly lower sensitivity in our study as compared to sputum sample could be due to the dilution of the organisms in the synovial fluid sample, as observed earlier by Negi et al Same factor could have contributed to sensitivity of 88.23% in IS6110 LAMP study on tuberculous meningitis, 70% in IS6110 LAMP study on tuberculous uveitis, and 85.7% in MPB64 LAMP study on intra‐ocular tuberculosis . Another study employing IS1081 LAMP assay on pleural fluid samples found a sensitivity and specificity of 48.7% and 83.3%, respectively . Such a low sensitivity can be explained by the presence of inhibitors in pleural fluid or the low copy number of IS1081 (5–7 repeats) in comparison to IS6110 (up to 25 repeats) …”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Slightly lower sensitivity in our study as compared to sputum sample could be due to the dilution of the organisms in the synovial fluid sample, as observed earlier by Negi et al Same factor could have contributed to sensitivity of 88.23% in IS6110 LAMP study on tuberculous meningitis, 70% in IS6110 LAMP study on tuberculous uveitis, and 85.7% in MPB64 LAMP study on intra‐ocular tuberculosis . Another study employing IS1081 LAMP assay on pleural fluid samples found a sensitivity and specificity of 48.7% and 83.3%, respectively . Such a low sensitivity can be explained by the presence of inhibitors in pleural fluid or the low copy number of IS1081 (5–7 repeats) in comparison to IS6110 (up to 25 repeats) …”
Section: Discussionsupporting
confidence: 47%
“…13 Another study employing IS1081 LAMP assay on pleural fluid samples found a sensitivity and specificity of 48.7% and 83.3%, respectively. 23 Such a low sensitivity can be explained by the presence of inhibitors in pleural fluid or the low copy number of IS1081 (5-7 repeats) in comparison to IS6110 (up to 25 repeats). 11,24 Uniquely, our study envisages the importance of using more than one target in the diagnosis of OATB.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we evaluated LAMP, Xpert and SAT-TB assays for the diagnosis of TBP in PE culture positive patients, compared with PE smear and found that all these methods were suboptimal for the detection of MTB in PE, whereas each of them demonstrated high specificity. [27]. In a meta-analysis of 40 studies of NAATs for TBP, PAI et al reported that these tests had low sensitivities (43-77%), but high specificities (95%) [28].…”
Section: Discussionmentioning
confidence: 99%
“…Similar previous investigations of NAATs for detecting MTB in PE have also reported modest sensitivities (21)(22)(23)(24). (27). In a meta-analysis of 40 studies of NAATs for TBP, PAI et al reported that these tests had low sensitivities (43-77%), but high specificities (95%) (28).…”
Section: Discussionmentioning
confidence: 99%